Special Interest Tourism Research Trends in Indonesian Journals: A Review from Design to Analysis - Muharis, Muharis; Muhammad Taufik; Bagas Anggara; Abdul Muhid (Yayasan Literasi Sains Indonesia, 2025)
This study aims to map the trends and characteristics of special interest tourism research in Indonesia in the period 2020–2024. The method used is content analysis with a focus on six main aspects: number of publications per year, type of research, research subjects, tourism topics studied, data collection instruments, and data analysis methods. Data were obtained through a systematic search on Google Scholar on April 26, 2025 using the keyword